A case report on Nocardia cyriacigeorgica in renal transplant patient - Velamuri A; Fatima R; Eswaran SP; Bezawada SR (Journal of Medical and Scientific Research)
Nocardiosis is an opportunistic infection caused by Nocardia species (spp). Nocardia species are ubiquitous environmental saprophytes occurring in the soil, organic matter, and water. A 36-year-old, female, renal transplant recipient presented with cutaneous and cerebral symptoms of disseminated Nocardiosis. Prompt diagnosis and treatment of the case resulted in a favourable outcome. Nocardiosis is an important infection in transplant recipients, which should be diagnosed early so that appropriate therapy can be instituted.